Holocaust monuments and national memory cultures in France and Germany since 1989 : the origins and political function of the Vél d'Hiv in Paris and the Holocaust Monument in Berlin /: the origins and political function of the Vél d'Hiv in Paris and the Holocaust Monument in Berlin. (2005) - Unknown
No abstract available